1313_final_formulas - y 2 − y1 x 2 − x1 y − y1 = m( x...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: y 2 − y1 x 2 − x1 y − y1 = m( x − x1 ) y = mx + b C ( x) = cx + F R ( x ) = sx P ( x) = R ( x) − C ( x) a b If A = c d and D = ad − bc ≠ 0 m= then A −1 = 1 d − b . D − c a I = Pr t A = P(1 + rt ) r i= m n = mt A = P(1 + i ) n P = A(1 + i ) − n (1 + i ) n − 1 S = R i −n 1 − (1 + i) P = R i n( E ) n( S ) P( A I B) P( B | A) = P( A) P( A I B ) = P( A) ⋅ P( B | A) P( A I B) = P ( A) ⋅ P( B) for A and B independent. P( E ) = P( Ai ) ⋅ P( E | Ai ) P( A1 ) ⋅ P ( E | A1 ) + ... + P ( An ) ⋅ P( E | An ) where 1 ≤ i ≤ n . P( Ai | E ) = E ( X ) = x1 p1 + x 2 p 2 + ... + x n p n Var ( X ) = p1 ( x1 − µ ) 2 + p 2 ( x 2 − µ ) 2 + ... + p n ( x n − µ ) 2 σ = Var ( X ) P( E ) P( E c ) P( E c ) P( E ) P( E ) = a a+b R= P( µ − kσ ≤ X ≤ µ + kσ ) ≥ 1 − ( A U B) c = A c I B c 1 k2 P( X = x) = C (n, x) p x q n − x p + q =1 µ = np Var ( x) = npq iS (1 + i ) n − 1 Pi R= 1 − (1 + i ) − n ( A I B) c = A c U B c n( A U B) = n( A) + n( B ) − n( A I B) n!= n ⋅ (n − 1) ⋅ (n − 2) ⋅ ... ⋅ 3 ⋅ 2 ⋅ 1 0! = 1 n! P ( n, r ) = (n − r )! n! C ( n, r ) = r!(n − r )! P( E U F ) = P( E ) + P( F ) − P( E I F ) P( E c ) = 1 − P( E ) σ = npq 1 [1 + P(− z < Z < z )] 2 a−µ P ( X > a ) = P Z > σ b−µ P ( X < b ) = P Z < σ b−µ a−µ P ( a < X < b) = P <Z< σ σ P( Z < z ) = ...
View Full Document

This note was uploaded on 02/21/2012 for the course MATH 1313 taught by Professor Constante during the Spring '08 term at University of Houston.

Ask a homework question - tutors are online